Adult female football players have higher lumbar spine and hip bone mineral density than age- and body weight-matched controls - El Hage, R.; Chatah, R.; Moussa, E.; Theunynck, D. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The aim of this study was to compare lumbar spine, total hip, femoral neck, total forearm and 1/3 Radius bone mineral density (BMD) in young female football players and age- and body weight- matched female controls (aged 18 to 30 years).